Mobile health application for breast examination awareness using health belief model - Jaya, Fatin Arryana Nasution Karta (2022)
Breast cancer (BC) is the most common cancer diagnosed among women in Malaysia. The late diagnosis is associated with educational background, the social history of BC and ineffective health promotion strategies. The purpose of this study is to develop a personalized and interactive mobile application using the Health Belief Model (HBM) for breast examination awareness. Mixed-method research was conducted in the Health Campus, Universiti Sains Malaysia (USM) during Phase I and III. Purposive sampling was used to recruit participants [public women attending hospital services; Hospital USM breast cancer content experts (oncology nurse, oncology counsellor and breast surgeon); and USM Health Campus software experts (Centre of Knowledge, Communication and Technology staff] (n=37) according to the inclusion and exclusion criteria. An appointment was arranged according to participants’ preference time and location. The time taken for each interview session is approximately 30-45 minutes. In Phase I, in-depth qualitative interviews and observation were used to identify the requirements for the mobile application. In Phase II, a mobile application (BrAware) was designed and developed based on the primary need and observation obtained in Phase I using HBM. In Phase III, the usability study was conducted to validate BrAware mobile application as a health promotion tool using the quantitative approach. The themes that emerged from the thematic analysis are vulnerability, forecasting, reactive, influence, outcome and obstacles. It was observed that the mobile application requirements were infographics, video animation, valid information, attractive features, and design. Meanwhile, observation of the available apps revealed that attention was given to perceived threat and benefit but lacking on the perceived barrier. The mean usability score of BrAware was 85.47 (SD 11.84), which shows a good mobile app. This study utilized data from the public women, content, and software experts in designing and developing BrAware. It is a mobile application integrated with health theory to promote self-awareness on BSE routine, educate on signs, symptoms and act as a monthly reminder device for early detection of breast cancer to improve survival and quality of life.